2003
DOI: 10.1021/jm020536q
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Design, Synthesis, and Evaluation of Novel Nonsteroidal Phenanthrene Ligands for the Estrogen Receptor

Abstract: Although there are many estrogen receptor antagonists with improved tissue selectivity profiles compared with tamoxifen, optimal tissue selectivity has not yet been demonstrated. As such there is still a need for additional diversity and new chemical scaffolds to allow for exploration of improved tissue selectivity. Here, we describe the discovery of a novel phenanthrene scaffold for estrogen receptor ligands utilizing a ligand based de novo design approach. The nanomolar binding of phenanthrenes, 12b,c, 14b,c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Because tamoxifen is generally described to have antagonist activity at the estrogen nuclear receptors ERα and ERβ and agonist activity at the G protein-coupled estrogen receptor GPR30, we attempted to replicate these results using selective agonists/antagonists. In these studies, NET production was not observed in response to treatment with MPP or PHTPP (selective ERα and ERβ antagonists, respectively 12 , 13 ), G-1 (a GPR30 agonist 14 ) or fulvestrant (a SERM that mimics the mixed agonist/antagonist characteristics of tamoxifen 15 , 16 ) ( Supplementary Fig. 3 ), indicating that tamoxifen-induced NET production is mediated by an estrogen receptor-independent mechanism.…”
Section: Resultsmentioning
confidence: 93%
“…Because tamoxifen is generally described to have antagonist activity at the estrogen nuclear receptors ERα and ERβ and agonist activity at the G protein-coupled estrogen receptor GPR30, we attempted to replicate these results using selective agonists/antagonists. In these studies, NET production was not observed in response to treatment with MPP or PHTPP (selective ERα and ERβ antagonists, respectively 12 , 13 ), G-1 (a GPR30 agonist 14 ) or fulvestrant (a SERM that mimics the mixed agonist/antagonist characteristics of tamoxifen 15 , 16 ) ( Supplementary Fig. 3 ), indicating that tamoxifen-induced NET production is mediated by an estrogen receptor-independent mechanism.…”
Section: Resultsmentioning
confidence: 93%
“…SignalGene explored the use of phenantrenes as SERMtype ligands for the estrogen receptors [68]. All of the phenantrenes prepared showed very low affinity for either ER.…”
Section: Phenantrenesmentioning
confidence: 99%
“…These ER ligands are then tested in vivo to determine whether they act as SERMS in particular tissues [4][5][6][7][8][9]. Traditionally, ER ligands have been identified using estrogen competition assays, which use radio-or fluorescently labeled estrogen [5,[10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%